2018
DOI: 10.3390/f9030106
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Focusing Effects of Microwaves inside Wood Due to Timber Ring Structure

Abstract: Abstract:The aim of this study is the detailed calculation of microwave propagation inside raw timber in cylindrical configurations. Two different approaches have been used. The first one uses an exact formulation and analytical approximations in order to explore the electromagnetic field distribution inside dry wood. The introduction of conductivity in the exact model makes it so complex that the equations are unsuitable for analytical manipulation. In order to further explore the effect of moisture in cylind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Although the focus of this paper is to present only experimental research, some numerical studies are also highlighted. Authors such as Hansson et al [34], Hansson et al [35], Brodie [17], Li et al [36], and Sanchez-Montero et al [30] developed numerical studies regarding the heat and MC movement in wood samples and the MW propagation inside wood samples.…”
Section: Treatment and Its Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the focus of this paper is to present only experimental research, some numerical studies are also highlighted. Authors such as Hansson et al [34], Hansson et al [35], Brodie [17], Li et al [36], and Sanchez-Montero et al [30] developed numerical studies regarding the heat and MC movement in wood samples and the MW propagation inside wood samples.…”
Section: Treatment and Its Applicationsmentioning
confidence: 99%
“…It is necessary to comprehend how microwaves interact with materials in order to understand the dielectric properties of wood and to determine the amount of energy absorbed by wood [9,12,30,31]. Due to the MC of wood, dielectric heating affects the wood through its entire profile [32].…”
Section: Introductionmentioning
confidence: 99%
“…Even the very good professional simulation tool used for this example (electromagnetic tool HFSS from Ansys Electronics Desktop 2020 75 ) has difficulties with complex effects like certain boundary conditions or fractional derivatives, among others, so that, in general, a previous theoretical analysis is always advisable to check the accuracy of simulation tools, as was conducted in references. 76,77 However, for this case, the complexity of the geometry and the number of different materials make simulation a more practical tool than theoretical analysis. Simulations of both WPT candidate antennas behavior, without and with the motor attached, are shown in Figures 4 and 5, and their comparison with real behavior should be performed in later tests.…”
Section: Step 7 Simulate Every Electromagnetic Interactionmentioning
confidence: 99%
“…As reported in [6], three-dimensional numerical simulations using commercial software were performed to profile the electromagnetic field at 3 GHz inside a cylindrical wood structure. The study reported the effect of the wood grain angle, the circular annual rings, and the effective permittivity of wood on the electric field distribution inside the wood cylinder.…”
Section: Introductionmentioning
confidence: 99%